ANALISIS HUBUNGAN ANTARA SEKTOR EKONOMI BERBASIS KERAKYATAN DENGAN PERTUMBUHAN EKONOMI INDONESIA - Nandang Najmulmunir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2005)
In the 1987 Indonesia having face the economical crisis. It had implicated to decreasing of the economical output, increasing of the number of unemployment and the poor, and the crisis of political agenda. Labour intensive sector or people economic sector can be enforced to accclcratc the economic growth and to over came many economic problems.